The Incidental Influence of Memories of Past Eating Occasions on Consumers’ Emotional Responses to Food and Food-Related Behaviors - Piqueras-Fiszman, Betina; Jaeger, Sara R. (Frontiers in Psychology, 2016)
Our memories of past eating experiences are influential in shaping food preferences and consumption behaviour, and the emotions that people associate to these memories are linked to their attitudes towards foods and their everyday food-related behaviours. This work studies the impact that food-related memories have on peoples’ emotional state and how this state is projected in a subsequent evaluation of images pertaining to food and food-related behaviours. Focus is placed on guilt and shame emotions. Through an online survey, three memories were investigated (a positive meal, a routine evening meal, and an overeating occasion) among U.K. consumers (N = 710). Participants primed with the overeating memory evaluated images related to junk food as conveying more feelings of guilt and shame than did participants primed with the memory of a positive meal. Moreover, this effect was moderated by participants’ dietary restraint status. Participants classified as having a high dietary restraint had stronger associations with the emotions guilt and shame than participants classified as low in dietary restraint. In contrast, a memory of a positive meal did not lead to positive valuations of any of the food-related images shown. Overall, the findings from the present study illustrate the partial impact that personal food memories have on consumers’ emotional response towards food-related issues, which in turn has the potential to affect future behaviour. This study therefore contributes to the literature about cognitive effects on food attitudes and behaviour. Furthermore, the results suggest that the empirical approach may be tapping into possibly unconscious emotions towards foods and food-related behaviour.